Implementasi Algoritma Playfair Dan Discrete Wavelet Transform Dalam Penyisipan Teks Pada Citra Digital - Setiawan, Indra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Cryptography is a technique for encoding messages and watermarking is a technique for hiding messages on a digital media. This combination is used as a system to secure messages because messages undergo two security processes, namely encryption and insertion into a digital image. The image used as the cover object is a JPEG image format. The characters used in the encryption process are the use of the 5x5 table. In the insertion process, message bits are added which have been converted into binary form, and are inserted at the end of the binary image. The result of this thesis is that the message that will be inserted in the text into the image will be encrypted first and converted into binary, without changing the shape of an image.